2006
DOI: 10.1016/j.fm.2005.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial resistance of Salmonella enteritidis and other salmonellas in the eggs and egg-storing trays from retails markets of Coimbatore, South India

Abstract: A study was conducted to determine the incidence of Salmonella enterica serovar Enteritidis and other Salmonella serovars on eggshell, egg contents and on egg-storing trays. A total of 492 eggs and 82 egg-storing trays were examined over a period of 1 year from different retail outlets of a residential area of Coimbatore city, South India. Salmonella contamination was recorded in 38 of 492 (7.7%) eggs out of which 29 was in eggshell (5.9%) and 9 in egg contents (1.8%). Around 7.5% of the egg-storing trays were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
61
4
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 27 publications
24
61
4
4
Order By: Relevance
“…The Salmonella isolation rate from inner parts of the eggs is higher than the shell rate, contrary to the similar previous studies, which have lower or 0% inner rate compared to higher shell rates (4,8,12,28). This difference could be the result of many contributing factors in those studies and our study, and cannot be extrapolated further.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…The Salmonella isolation rate from inner parts of the eggs is higher than the shell rate, contrary to the similar previous studies, which have lower or 0% inner rate compared to higher shell rates (4,8,12,28). This difference could be the result of many contributing factors in those studies and our study, and cannot be extrapolated further.…”
Section: Discussioncontrasting
confidence: 97%
“…Our ISO results indicated that 10.9 % of inner and 5.9 % of shell (overall 15.8 %) of the retail eggs harbored Salmonella. Our inner part rate is higher than previous studies reported from different parts of the world (4,8,12,19,28), which have found this rate as 0-7.4 % in retail eggs, contrary to a study by Betancor et al (2), indicating a considerably higher rate of 35% Salmonella from Uruguay. Similarly, there are several previous studies with lower Salmonella shell rates as 0-5.3% (4,12,24) than ours, two studies with higher rates as 15.8% (21) and 21% (8), and one study by Suresh et al (28) indicating a slightly higher rate as 6.1% than ours.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…However, the results from this study does not agree with studies carried out by [23] who reported a 57.1% sensitivity to amoxycillin, whereas a 100% resistance rate was recorded in this present study. Resistance to Oxacillin is in agreement with studies carried out by [24,23]. The isolates were resistant to Streptomycin showing a resistance rate of 51.4%.…”
Section: Discussionsupporting
confidence: 89%
“…These animal-adapted serotypes show a much higher predilection for causing invasive disease in humans [1]. Contaminated raw foods (meat, eggs, milk) and infected animals are important sources of human infections [1,[3][4][5]. In general, antimicrobial therapy is not recommended for gastroenteritis caused by NTS in humans, however, it is indicated for invasive salmonellosis [1,2].…”
Section: Introductionmentioning
confidence: 99%